Respuesta :

Answer:

The following expressions become negative:

  • 1) x+y = 1+(-2) = -1
  • 3) x times y = xy = (1)(-2) = -2
  • 4) x divided by y = x/y = 1/-2 = -2

Step-by-step explanation:

Given

  • x = 1
  • y = -2

Computing by substituting x = 1, and y = -2

1) x+y = 1+(-2) = -1

2) x - y = 1 - (-2) = 1+2 = 3

3) x times y = xy = (1)(-2) = -2

4) x divided by y = x/y = 1/-2 = -2

It is clear from the above calculations that when we put x = 1, and y=-2 then the expressions (x+y), (x times y), and (x divided by y) become negative.

Therefore, the following expressions become negative:

  • 1) x+y = 1+(-2) = -1
  • 3) x times y = xy = (1)(-2) = -2
  • 4) x divided by y = x/y = 1/-2 = -2
ACCESS MORE